Functional interaction of abnormal beta and gamma oscillations on bradykinesia in parkinsonian rats - Xinxin Jiang; Jian Yang; Zirui Wang; Jun Jia; Gang Wang (Brain Research Bulletin, 2024)
Bradykinesia, a debilitating symptom characterized by impaired movement initiation and reduced speed in Parkinson’s disease (PD), is associated with abnormal oscillatory activity in the motor cortex-basal ganglia circuit. We investigated the interplay between abnormal beta and gamma oscillations in relation to bradykinesia in parkinsonian rats. Our findings showed reduced movement activities in parkinsonian rats, accompanied by enhanced high beta oscillations in the motor cortex, which are closely associated with movement transitional difficulties. Additionally, gamma oscillations correlated with movement velocity in control rats but not in parkinsonian rats. We observed selective coupling between high beta oscillation phase and gamma oscillation amplitude in PD, as well as cortical high beta-broadband gamma phase-amplitude coupling (PAC) negatively influencing locomotor activities in control and PD rats. These findings suggest a collaborative role of cortical beta and gamma oscillations in facilitating movement execution, with beta oscillations being linked to movement initiation and gamma oscillations associated with movement speed. Importantly, the aberrant alterations of these oscillations are closely related to the development of bradykinesia. Furthermore, PAC hold promise as a biomarker for comprehensive assessment of movement performance in PD.